COPD exacerbation: factors influencing hospitalization duration - Gashynova K.Yu. (Medičnì Perspektivi)
Studying the causes of hospitalization prolongation terms in COPD exacerbation may help optimize treatment, reduce expenditures on the patient and avoid episodes relapses. The aim of the work was to determine the factors affecting the length of hospitalization due to COPD exacerbation. A retrospective analysis of medical records of inpatients hospitalized with COPD exacerbation to therapeutic department of CI "Dnipropetrovsk municipal clinical hospital N 6" of “Dnipropetrovsk regional council" during three years was done. It was found that age, height, number of comorbidities, presence of any symptoms or changes in laboratory analyses do not affect the duration of hospitalizations due to COPD exacerbations. Regardless of the frequency of hospital admissions, length of hospitalization moderately positively and reliably correlates with the disease stage (R = 0,516, p <0,001). Decrease of respiratory function indices, especially FEV1, significantly increases the length of stay in the hospital both in case of one (R = -0,457, p <0.001) or multiple hospitalization during three years (R = -0,512, p <0.001). Reduced body weight and low body mass index during hospitalization are prognostically unfavorable factors, because these parameters, though weakly, but reliably negatively correlate with the number of days spent in the hospital (R = -0,195, p = 0,028 and R = -0,246, respectively, p = 0,005). In the population of patients hospitalized due to COPD exacerbation, moderately positive reliable correlation (R = 0,392, p <0,001) between the length of hospital stay and number of hospitalizations during three years was established. The dependence of hospitalization duration in COPD exacerbations on patient’s gender requires further investigation.